Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater - Pinto, Clara A.; Nadezhdina, Nadezhda; David, Jorge S; Kurz-Besson, Cathy; Caldeira, Maria C; Henriques, Manuel O; Monteiro, Fernando G; Pereira, João S; David, Teresa S (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.
Keywords: Cork oak; ecohydrology; sap flow radial profile; tree water sources; tree water use; water balance

Disentangling drought-induced variation in ecosystem and soil respiration using stable carbon isotopes. - Unger, Stephan; Máguas, Cristina; Pereira, João S; Aires, Luis M; David, Teresa S; Werner, Christiane (Oecologia, 2010)
Combining C flux measurements with information on their isotopic composition can yield a process-based understanding of ecosystem C dynamics. We studied the variations in both respiratory fluxes and their stable C isotopic compositions (delta(13)C) for all major components (trees, understory, roots and soil microorganisms) in a Mediterranean oak savannah during a period with increasing drought. We found large drought-induced and diurnal dynamics in isotopic compositions of soil, root and foliage respiration (delta(13)C(res)). Soil respiration was the largest contributor to ecosystem respiration (R (eco)), exhibiting a depleted isotopic signature and no marked variations with increasing drought, similar to ecosystem respired delta(13)CO(2), providing evidence for a stable C-source and minor influence of recent photosynthate from plants. Short-term and diurnal variations in delta(13)C(res) of foliage and roots (up to 8 and 4 per thousand, respectively) were in agreement with: (1) recent hypotheses on post-photosynthetic fractionation processes, (2) substrate changes with decreasing assimilation rates in combination with increased respiratory demand, and (3) decreased phosphoenolpyruvate carboxylase activity in drying roots, while altered photosynthetic discrimination was not responsible for the observed changes in delta(13)C(res). We applied a flux-based and an isotopic flux-based mass balance, yielding good agreement at the soil scale, while the isotopic mass balance at the ecosystem scale was not conserved. This was mainly caused by uncertainties in Keeling plot intercepts at the ecosystem scale due to small CO(2) gradients and large differences in delta(13)C(res) of the different component fluxes. Overall, stable isotopes provided valuable new insights into the drought-related variations of ecosystem C dynamics, encouraging future studies but also highlighting the need of improved methodology to disentangle short-term dynamics of isotopic composition of R (eco).
Keywords: Drought; Ecosystem respired carbon dioxide stable isotopic; Keeling plots; Mediterranean ecosystem; Respired carbon dioxide